The relationship between multidimensional poverty and armed conflict : the case of Antioquia, Colombia (2014)
BASTRACT: This paper analyzes the relationship between poverty and armed conflict in Antioquia, Colombia. The poverty analysis is framed within Sen’s capability approach, which forms the conceptual basis of the multidimensional poverty index (Alkire and Foster, 2011). The MPI is measured with data from a government database called SISBEN, used to target social assistance programs, while the armed conflict is measured through count data about violent events during the period 1996-2010 on each municipality. The possible existence of a relationship between poverty and armed conflict is analyzed through exploratory and non¬parametric methods. The results so far suggest that the MPI is robust to the multidimensional cut off. Also, they show that those areas more affected by conflict usually showcase high levels of multidimensional poverty.